A simple diagnostic model to estimate total sink recharge based on dye tracing experiments - Hong Liu; Guangquan Li (Acta Carsologica, 2015)
Dye tracing experiments are an active, effective and promising approach to investigate karst aquifers. In this paper, we develop a simple diagnostic model for calculating total recharge of sinks using dye tracing results. The conceptual model is that all sinks are convergent to a major conduit which then branches into several conduits and finally to several springs. Under the assumption that advection is dominant over dispersion at springs, breakthrough curve at a single spring can be used to calculate total recharge. The model is advantageous in that for such a conduit network, it is not necessary to measure breakthrough curves at all springs. Then the model with two dye tracing experiments is used to infer the conduit network in a karst aquifer in Luxi, southwest China. This paper represents a preliminary effort aiming to using dye tracing results to calculate the total recharge of sinks and infer the network of conduits.